Men in White: A Narrative Inquiry of Male Nurse Stereotype in Nursing - Antiporda, Chenn Martin L.; Francisco, Jhoechell P.; Lagrama, Generey G.; Maghirang, Brent B.; Malicad, Jorge Dwight L. (International Journal of Qualitative Research, 2024)
Nurses have been traditionally all seen as a predominantly female profession in the healthcare industry resulting in men remaining a minority and gender stereotypes in their workplace. Thus, this narrative inquiry aims to explore the men’s experiences, the challenges they faced, and the coping strategies they used in the field of nursing. A semi-structured questionnaire was used for in-depth interviews with the four participants; ages 32 to 37 years old, who were selected through snowball sampling. The data were further understood through the application of thematic analysis. The recorded interview was transcribed and coded. Categories were clustered; then, emerging themes were derived. Based on the findings, there are still some male nurses who are facing challenges in hospital settings due to these stereotypes that limit the practice of male nurses. However, despite these challenges, some male nurses still managed to pursue nursing due to their passion and job opportunities, and having coping strategies such as peer and family support and balancing work and life. In conclusion, despite the stereotyping that male nurses may face, their passion for nursing, job opportunities, and effective coping strategies enable them to succeed in the nursing profession.